npj Systems Biology and Applications - Jolly, Mohit Kumar; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Systems Biology and Applications considers all aspects of research covering computational and mathematical approaches to analysis and modeling of complex biological systems. The journal covers a broad range of topics including but not limited to: Computational modeling of biological systems Application of systems biology approaches to disease modeling, pharmacology, drug discovery, biotechnology, and industry Network biology and interactome analysis Multi-omics data integration Synthetic biology and metabolic engineering Single-cell systems biology Systems immunology and host-pathogen interactions Systems neuroscience and brain function Environmental systems biology Evolutionary systems biology The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by systems biology experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Life sciences; Bioinformatics; Bioinformatics; Life Sciences; Computational and Systems Biology; Bioinformatics